Atlas of the Tethyan orthophragmines - Özcan, Ercan; Yücel, Ali Osman; Erkızan, Levent Sina; Gültekin, Münire Nur; Kayğılı, Sibel; Yurtsever, Sıla (Springer Science and Business Media B.V., 2022)
Orthophragmines are a group of discoidal, lenticular or stellate ‘orbitoidal’ larger benthic foraminifera that thrived in shallow-marine environments in low-to-middle latitudes during the late Paleocene and Eocene. They consist of two phylogenetically independent families with similar morphology, such as Discocyclinidae (with two Tethyan genera—Discocyclina and Nemkovella) and Orbitoclypeidae (with three genera—Orbitoclypeus, Asterocyclina and Hexagonocyclina in the Tethys) distinguishable by the different microspheric juvenarium of the microspheric (B) forms. Sixty-one species of orthophragmines are herein described and illustrated based on material from various Tethyan localities in Europe, North Africa, Turkey, the Arabian Peninsula, the Indian Subcontinent and SE Asia. Thirty-two species of Discocyclina, six species of Nemkovella, thirteen species of Orbitoclypeus, nine species of Asterocyclina and one species of Hexagonocyclina are included. Some species include chrono-subspecies, established by applying the principles of embryonic and nepionic acceleration in the megalospheric (A) forms, primarily expressed by the increase in the size of the deuteroconch, morphological modifications forming various embryonic configurations through the phylogeny, and the increase in the number of adauxiliary chamberlets that arise from the embryonic apparatus. This study is mainly based on investigating oriented sections of many free specimens, and some random rock thin sections where obtaining free tests of orthophragmines was not possible. The Atlas is designed as a laboratory handbook for micropaleontology students and a guidebook to assist professionals with the easy identification of orthophragmines in thin sections. © 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Asterocyclina; Discocyclina; Hexagonocyclina; Nemkovella; Orbitoclypeus; Orthophragmines; Systematics